Hubungan Efikasi Diri dengan Self-Regulated Learning pada Siswa Homeschooling - Sofi Anggraini; Muslimah Zahro Romas; Dewi Handayani Harahap (Jurnal Psikologi, 2025)
This study aims to examine the empiricial relationship between self-efficacy and self-regulated learning among high school students in Homeschooling Entrepreneur Yogyakarta. The hypothesis is a positive correlation between self-efficacy and self-regulated learning on students homeschooling. Subject in this study was 34 students high school Homeschooling Entrepreneur Yogyakarta. The research using a saturated sampling technique. The research instruments include the Motivated Strategies for Learning Questionnaire (MSLQ) for measuring self-regulated learning and a validated self-efficacy scale, both of which have demonstrated reliability. Data analysis employs the product-moment correlation technique. The results showed no significant relationship between self-efficacy and self-regulated learning among the students, shown by a correlation value of rxy = 0.191 and a significance level of 0.140 (p>0.01). Consequently, the hypothesis is rejected based on these findings.